Relações federativas e o regime de colaboração: desafios no financiamento da educação pública municipal de Parnamirim/RN (2009-2016) - Lima, Amilka Dayane Dias Melo (2019)
This thesis aims to analyze the financing of the municipal public education network of the municipality of Parnamirim / RN, in the context of federative relations and the collaboration regime, in the period 2009-2016. The study is based on the federative dynamics that involves the financing of basic education after the Federal Constitution of 1988, comprising the collaboration regime as a necessary mechanism to balance the tensions in the educational offer, due to the asymmetry regarding the capacity of self-financing among the federated entities, the legacy of the inequality of income distribution and the discrepancy of the tax potential between the regions. The theoretical methodological support is aligned with the qualitative approach and documentary research based on: the legislations of the state of RN and Parnamirim / RN prefecture, referrals to the programs of the National Fund for Education Development (FNDE), Summary Report on Budgetary Execution - Information System on Public Budgets in Education (SIOPE), Synopsis Statistics of the School Census of the National Institute of Studies and Educational Research Anísio Teixeira (INEP); Microdata from the School Census and Indicators of Educational Development, also from INEP. The results indicate that, in Brazil, the public resources of the education systems show limitations on the federative balance. In the specific context of the municipal public school network of Parnamirim / RN, the occurrence of the collaboration scheme in its financing is partial, being more evident between 2009-2013. Starting in 2014, there is a greater imbalance between the contribution of each entity versus its fiscal capacity. This phenomenon occurs due to the progressive decrease of the Union's actions in the financing of this network. It is worth noting that although the establishment of the collaboration regime deserves qualifications, it has guaranteed growth above the inflation of resources for the financing of municipal education, through automatic constitutional transfers, Fund for Maintenance and Development of Basic Education and Valorization of Professionals (Fundeb) and additional resources from programs developed from government policies of the Union via FNDE programs. The increase in resources had an impact on the growth of expenditure on Maintenance and Development of Education (MDE), allowing greater investment by students enrolled. In this movement, there was a decrease in the number of students enrolled in the municipal education network, while the number of schools, teachers and classes increased. The data show that the collaboration regime had positive repercussions on educational data. However, this same phenomenon did not occur with indicators of educational development, such as the Basic Education Development Index (IDEB), income rates (approval, disapproval and abandonment), age / grade distortion rate and student average per class.